American meat and its influence upon the public health / by Albert Leffingwell. - Leffingwell, Albert, 1845-1916. (Tufts University. Tisch Library., 2015)
1 online resource (vii, 208 pages); Includes index.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.